TOMADA DE DECISÃO ENTRE A PRODUÇÃO DE ÁGUA NÃO POTÁVEL EM EDIFÍCIOS RESIDENCIAIS E ÁGUA POTÁVEL NO SISTEMA PRODUTOR SÃO LOURENÇO - Patucci, Renato; Oliveira, Lúcia; Kurokawa, Fernando; Mielli, Viviane (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The population growth and the climatic variability is contributing to the amount of population living in water stress. There are alternative sources of non-potable water that can attend part of the residential demand like the reclaimed water. The aim of this study is to formulate a mathematical model for decision making between the enlargement of traditional centralized potable water system and the implementation of non-potable water systems (NPWS) in the metropolitan area of São Paulo. By bibliographic review it was verified that around 20% of water domestic uses are for non-potable needs. It was collected data of construction, operation and maintenance of a non-potable water building system and of a potable water centralized São Lourenço Production System (SLPS). The simulation made for the first 20 years of operation, showed that the SLPS has the lowest accumulated costs, but 10 buildings sharing a centralized NPWS have relatively close values to the SLPS, so other factors, such as environmental performance, can be decisive in choosing the most appropriate solution.